Development of Teaching Materials in Writing Poetry Based on Local Wisdom in Class X Students of Gema Bukit Vocational School, Barisan Tanjung Morawa - Manurung, Noviani Manda Sari; Prihandani, Nugroho; Sutikno, Sutikno (TIN: Terapan Informatika Nusantara, 2020)
This study aims to determine the development of poetry-based teaching materials based on local wisdom in class X SMK Gema Bukit Barisan Tanjung Morawa. This research uses the R & D method. The subjects in this study were students of class X-1 SMK Gema Bukit Barisan Tanjung Morawa, the 2017-2018 school year totaling 36 students. The steps used in this study are collecting data, designing products, validating experts, revising products. Based on the product effectiveness test conducted on the media, it is known that local wisdom-based learning media is effectively used in the learning process. This is evidenced by the results of the effectiveness of local wisdom-based learning media products that have an effectiveness of 84.28% with a very good category. Based on the results of the tests conducted, it is known that the learning outcomes of students who use multimedia-based learning media are higher than students who use multimedia learning-based learning media. this is evidenced by the acquisition of the average value of students who learn using interactive multimedia-based learning media has an average value of 84.3 while students who learn by using local wisdom-based learning media obtain an average score of 65.1.